Content Marketing Strategy To Maximize Sme Sales Performance - Ramadhan, Ahmad; Mashduqi, Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study analyzes content marketing strategies to maximize sales of MSME products in North Sumatra. Using an exploratory qualitative approach, this study involved 10-15 MSMEs in the food, craft, and fashion sectors that actively use digital platforms. Data was collected through semi-structured in-depth interviews and analyzed using thematic analysis techniques to identify patterns of content marketing strategies. Findings showed that local culture-based strategies, such as storytelling and collaboration with micro-influencers, increased customer engagement by 40% and sales conversion by 24%. Visual content optimization on platforms such as Instagram and Facebook also proved effective. The implication is that MSMEs need to integrate artificial intelligence-based personalization technologies and utilize digital training to enhance their competitiveness. This research encourages policymakers to provide digital training incentives to support the adoption of technology by MSMEs. Limitations of the study include a limited sample size and a geographical focus on North Sumatra, so further research with broader coverage is needed.